Phonological Errors in the Recitation of Surah Al-Baqarah Verses 1-5 by Indonesia Vocalist: A Phonetic and Phonological Analysis - Farnaz, Taliah Aqilah; Zahra, Azizatiz; Hilmi, Danial (International Journal Labs, 2025)
This study analyzes phonological errors in the recitation of Surah Al-Baqarah verses 1-5 by Indonesian vocalist “NB” through a YouTube video. The research focuses on identifying errors in sound production, particularly related to makhraj (articulation points) and the characteristics of letters, as well as deviations in pronunciation. The method used is descriptive qualitative with content analysis and free listening techniques. The results reveal 13 phonological errors, including letter substitutions (e.g., ? replaced with ?), phoneme additions, and stress (Nabr) errors. These errors stem from a lack of understanding of makhraj and letter characteristics, as well as interference from the speaker's native language. The impact of these errors not only disrupts the clarity of recitation but also risks altering the meaning of the verses. This study emphasizes the importance of in-depth learning of phonology and tajwid to prevent the fossilization of phonological errors, especially for non-native Arabic learners. The findings are expected to serve as a reference for developing more effective methods for teaching the pronunciation of Hijaiyah letters.